Liberalizacja handlu usługami. Czy GATS spełnia nadzieje? - Rymarczyk, Jerzy (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The author of the paper evaluates effects of the negotiations on liberalization of international trade of services that have been taking place within the General Agreement on Trade of Services (GATS). He concludes that in the time period of ten years, which passed since closing the Uruguay Round, the progress in negotiations referred to is rather slight and points out reasons for it. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 327-335